The Impact of Hybrid Learning on Psychological Wellness, Academic Performance, and Health Behaviors Among Medical Students - Maria Mughal, Minahil Fatima, Memoona Faisal, Kinza Zaheer, Ayesha Tariq, Rabia Khurram (International Journal of Pharmacy Research & Technology (IJPRT), 2026)
Hybrid learning, combining traditional faceto-face teaching with digital educationplatforms, has become a widely adoptedinstructional model in medical education. While it offers flexibility and improvedaccess to learning resources, its impact onpsychological wellness, academicperformance, and health behaviors remains